Efficient transformation and artificial miRNA gene silencing in Lemna minor. (2nd July 2014) - Cantó‐Pastor, A.; Mollá‐Morales, A.; Ernst, E.; Dahl, W.; Zhai, J.; Yan, Y.; Meyers, B. C.; Shanklin, J.; Martienssen, R.
Abstract: Despite rapid doubling time, simple architecture and ease of metabolic labelling, a lack of genetic tools in the Lemnaceae (duckweed) has impeded the full implementation of this organism as a model for biological research. Here, we present technologies to facilitate high‐throughput genetic studies in duckweed. We developed a fast and efficient method for producing Lemna minor stable transgenic fronds via Agrobacterium ‐mediated transformation and regeneration from tissue culture. Additionally, we engineered an artificial microRNA (amiRNA) gene silencing system. We identified a Lemna gibba endogenous miR166 precursor and used it as a backbone to produce amiRNAs. As a proof of concept we induced the silencing of CH42, a magnesium chelatase subunit, using our amiRNA platform. Expression of CH42 in transgenic L. minor fronds was significantly reduced, which resulted in reduction of chlorophyll pigmentation. The techniques presented here will enable tackling future challenges in the biology and biotechnology of Lemnaceae.